Crossing the Real and Virtual Worlds: Adaptation of the Transfer Phenomena Scale Game (GTPS-20) - Richard Noya; Heru Astikasari Setya Murti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The gaming industry in Indonesia is rapidly expanding, with a growing number of players, highlighting the need for appropriate instruments to understand its impact. This study aimed to adapt the Game Transfer Phenomena Scale (GTPS-20) into Indonesian and evaluate its psychometric properties. The adaptation process followed standard procedures, including forward translation, synthesis, backward translation, expert judgment, pretest, and submission, and was tested on 823 gamers across Indonesia. Results indicated that the Indonesian GTPS-20 demonstrated high content validity (0.93–1.00), strong item discrimination (0.608–0.756), excellent reliability (α = 0.956), and satisfactory construct validity based on confirmatory factor analysis (RMSEA = 0.023; SRMR = 0.037; CFI = 0.998; TLI = 0.998). These findings confirm that the adapted scale is a valid and reliable tool for assessing game transfer phenomena among Indonesian gamers and can support future research on the psychological and behavioral impacts of gaming. Keywords: game transfer phenomena, instrument adaptation, confirmatory factor analysis, indonesian gamers